E-Learning and Its Role as a Learning Media in Education and Training - Kholil, Muhammad; Sofyan, Herminarto; Surjono, Herman Dwi (Universitas Negeri Malang, 2020)
This study examines the use of e-learning as a learning media in Education and Training. The role of e-learning in learning can bridge the gap between teachers and students in different spaces and times. The method used in this study is a literature review with a narrative review approach. The study result revealed that e-learning as a learning media is effective to improve student learning achievement. In the training of the company, the use of e-learning can also improve the performance of employees. E-Learning that uses MOOC (Massive Open Online Course) provides benefits for learners in formal education and companies who want to develop their abilities and careers. It is important to emphasize aspects of content, users, and the latest technology to optimize the effectiveness of implementing e-learning.